The Influence of Risk Perception on Business Model Innovation - Hamdani, Nizar Alam; Khalifah, Risti Nur (Rescollacom (Research Collaborations Community), 2023)
Entrepreneurship in Indonesia is believed to be poorly developed compared to other Asian countries. Many efforts have been done to foster the entrepreneurial spirit, particularly the ways to change the mindset of young people that when they graduate from universities, seeking for jobs is not the only option. They can also be entrepreneurs. The lack of students' interest in the business and entrepreneurship is influenced by the perception of risk in business model innovation. Risk perception is the evaluation of people's decision making that is associated with a particular scenario. This study aims to empirically examine the effect of risk perception on business model innovation and measure the influence level of risk perception on business model innovation. This analysis uses the independent variable; the perception of risk. The dependent variable is business model innovation.. The researchers set some criteria to choose some respondents such as the active status of students at Faculty of Entrepreneurship, Garut University. The reason for choosing the entrepreneurship students because they have learned more about entrepreneurial procedures so that they have a better understanding of risk perceptions of business model innovation. Researchers used a causal research design on 30 respondents. Data were collected by distributing online questionnaires via e-mail and analyzed using SPSS 25 software. The statistical method used simple linear regression analysis, with hypothesis testing the t-statistic test. The results of this study indicate that risk perception has a significantly positive effect on business model innovation. This research has an impact for business actors to continue to consider risk perceptions because it has an influence on business model innovation.